Pengaruh Model Pembelajaran Induktif Dalam Mata Pelajaran Pendidikan Agama Islam Terhadap Kemampuan Berpikir Kritis Peserta Didik - Salamudin, Ceceng; Alimi, Miftahul (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Critical thinking is a vital skill that needs to be nurtured and developed from a young age. However, many students still struggle to engage critically during the learning process, often refraining from expressing their opinions or asking questions about subjects they do not fully understand. This issue is primarily due to teacher-centered learning approaches, which limit opportunities for students to voice their thoughts and develop critical thinking skills. Therefore, the inductive teaching model is proposed as an effective solution to enhance students' critical thinking abilities. The aim of this study is to describe the impact of the inductive teaching model on critical thinking skills in Islamic religious education. This research investigates the correlation between the inductive teaching model and the development of critical thinking abilities among students. A quantitative descriptive approach was employed, involving data collection through observations and questionnaires distributed to 36 respondents. The data were analyzed using statistical methods. The results indicate that the implementation of the inductive teaching model in Islamic religious education achieved an average score of 4.41, which falls under the "very good" category. Similarly, students' critical thinking skills averaged 4.13, also categorized as "very good." These findings suggest that the inductive teaching model is an effective alternative to enhance students' critical thinking skills in Islamic religious education. Based on hypothesis testing, it was found that the inductive teaching model positively influences students' critical thinking abilities by 43.90%. The remaining 56.10% of the influence on critical thinking skills is attributed to other variables not included in this study.  Keywords: Inductive Teaching Model, Critical Thinking, Islamic Religious Education